1995
DOI: 10.1002/1097-0142(19950515)75:10<2427::aid-cncr2820751007>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transarterial targeted treatments on survival of patients with hepatocellular carcinoma. An Italian Experience

Abstract: Background. Most patients with hepatocellular carcinoma (HCC) are not suitable for surgical therapy. Systemic chemotherapy, immunotherapy, and hormonotherapy have not had convincingly acceptable results. Therefore, transarterial catheter‐targeted therapies such as intraarterial chemotherapy (IAC), possibly followed by transcatheter arterial chemoembolization (TACE), have been proposed. Methods. A survival analysis curve was drawn using the Kaplan‐Meier method for 164 patients, 100 with HCC who underwent TACE (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 30 publications
4
36
1
4
Order By: Relevance
“…Early recurrence following a CR achieved by TACE may be mainly attributed to residual tumors that were undetectable on angiography. The distribution of lipiodol uptake determined by tumor differentiation and the blood vessel network have been shown to affect the local recurrence rate and long-term outcome in patients with HCC (37,38). Furthermore, consistent with the present study, a previous study showed that local recurrence developed more frequently in patients with early recurrence (≤1 year) compared with those with late recurrence (>1 year) (27).…”
Section: Discussionsupporting
confidence: 90%
“…Early recurrence following a CR achieved by TACE may be mainly attributed to residual tumors that were undetectable on angiography. The distribution of lipiodol uptake determined by tumor differentiation and the blood vessel network have been shown to affect the local recurrence rate and long-term outcome in patients with HCC (37,38). Furthermore, consistent with the present study, a previous study showed that local recurrence developed more frequently in patients with early recurrence (≤1 year) compared with those with late recurrence (>1 year) (27).…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the factors that were significant in multivariate analysis were similar to the factors that constitute the CLIP score, and they also were similar to the factors determined in previous studies of TACE. 28,29 The most powerful prognostic factor of poor survival was vascular invasion in this study, and similar results were reported in patients who underwent liver resection or transplantation. 1,[30][31][32] Although the BCLC system was validated as the most suitable prognostic system for patients with HCC in Italy and the United States, it was not considered a suitable prognostic system in the Eastern countries until now.…”
Section: Discussionsupporting
confidence: 88%
“…We chose TAE and 5-FU as standard treatment before introducing pravastatin administration. TAE prevents tumour progression (Charnsagavej et al, 1983;Yamada et al, 1983;Stefanini et al, 1995) and is one of the standard treatments for unresectable HCC in Japan. 5-FU also has activity against HCC (Cavalli et al, 1981;Coi et al, 1984;Falkson et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…We administered pravastatin (40 mg day -1 ), for which the liver has a high affinity, to HCC patients in a randomized controlled trial after transcatheter arterial embolization (TAE) (Charnsagavej et al, 1983;Yamada et al, 1983;Stefanini et al, 1995) and oral 5-fluorouracil (5-FU) as standard treatment.…”
mentioning
confidence: 99%